1980
DOI: 10.1093/ajcn/33.10.2151
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C, vitamin B6, vitamin B12, folic acid, riboflavin, and thiamin on the breast milk and maternal status of well-nourished women at 6 months postpartum

Abstract: The effects of vitamin supplements and/or diet on the vitamin levels in milk of women were determined at 6 months postpartum. Six subjects consumed a daily supplement (Natalins, Mead-Johnson) in addition to a well-balanced diet--supplemented group, and six subjects consumed only a well-balanced diet--nonsupplemented group. The subjects expressed milk for 3 days at 4-hr intervals, 0, 4, 8, and 12 hr after awakening or taking their vitamin supplement. A 4-day diet record, fasting blood sample, and 24-hr urine sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…This is in accordance with earlier observations by Shapiro et al (1965), Keizer et al (1995) and Smith et al (1983). On the other hand, Thomas et al (1980) were unable to detect this difference in folate concentrations between supplemented and unsupplemented women, probably explained by the small number of participants in their cross-sectional study. The vitamin supplemented and the unsupplemented exclusively breast-feeding women were comparable with regard to other factors that can have an impact on the results.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is in accordance with earlier observations by Shapiro et al (1965), Keizer et al (1995) and Smith et al (1983). On the other hand, Thomas et al (1980) were unable to detect this difference in folate concentrations between supplemented and unsupplemented women, probably explained by the small number of participants in their cross-sectional study. The vitamin supplemented and the unsupplemented exclusively breast-feeding women were comparable with regard to other factors that can have an impact on the results.…”
Section: Discussionmentioning
confidence: 84%
“…Several investigations show an increased risk of suboptimal folate status (Matoth et al, 1965;Donangelo et al, 1989;Lehti, 1989;Ramlau-Hansen et al, 2003;Villalpando et al, 2003) and a reduction in folate stores during the lactation period (Shapiro et al, 1965;Tamura et al, 1980;Butte et al, 1981;Sneed et al, 1981;Smith et al, 1983;Dostalova, 1984;Bruinse et al, 1985;Bates et al, 1986;Salmenpera et al, 1986;Keizer et al, 1995;Mackey and Picciano, 1999) in women with no folic acid supplementation and with a diet insufficient in folate. Others have shown that lactation does not affect the level of folate (Cole et al, 1974;Thomas et al, 1980;Ek, 1983). A possible B12 depletion during lactation is apparently less common than folate depletion (Shapiro et al, 1965;Sneed et al, 1981;Dostalova, 1984;Donangelo et al, 1989;Keizer et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…There may be an intrinsic regulatory mechanism for the transfer of vitamin C from diet to breast milk to prevent excessive loads. At low intakes, there may be a dose-response effect, but above a certain saturation level, large supplement intakes are not reflected in breast milk vitamin C (Thomas et al, 1980;Byerley & Kirksey, 1985). Low vitamin C concentrations in breast milk were associated with a higher risk of atopy in the infant.…”
Section: Discussionmentioning
confidence: 98%
“…When comparing infants from multivitamin-supplemented mothers to infants from non-multivitamin-supplemented mothers, we found a major effect in serum vitamin B12 at 6 weeks that was sustained through 6 months of age. Observational studies had suggested that the vitamin B12 status of newborns is strongly associated with that of their mothers (Bjorke Monsen et al, 2001) and that correction of deficiencies through vitamin B12 supplementation among presumably HIV-uninfected mothers resulted in greater B12 concentrations in breast milk (Thomas et al, 1979(Thomas et al, , 1980Sneed et al, 1981). It has been described that vitamin B12 concentrations decrease in the newborn during the first 6-8 weeks (Bjorke Monsen & Ueland, 2003); our results suggest that maternal supplementation with multivitamins at multiples of the recommended dietary allowance (RDA) in USA could prevent such a decrease.…”
Section: Discussionmentioning
confidence: 99%